Increased femoral anteversion-related biomechanical abnormalities: lower extremity function, falling frequencies, and fatigue - Leblebici, Gökçe; akalan, ekin; Kuchimov, Shavkat Nadir; Kurt, Aslıhan; Temelli, Yener; Miller, Freeman; ÖNERGE, KÜBRA; APTİ, ADNAN (My University, 2019)
Background: Increased femoral anteversion (IFA) is defined as forwardly rotated femoral head relative to the transcondylar knee axis which may have a potential to reduce the functional quality of adolescents. Therefore, the aim of our study was to investigate the effects of IFA on lower-extremity function, falling frequency, and fatigue onset in neurologically intact children. Research question: Does increased femoral anteversion influence lower extremity function, falling frequency and fatigue on set in healthy children? Methods: Sixty-five participants with increased femoral anteversion (IFA) and thirty-two healthy peers as control were included into the study. For the function, the lower extremity function form (LEFF) which is adapted from Lower Extremity Function Test used. Falling frequency and fatigue onset time were assessed by a Likert-type scale. In addition, the activities which cause frequently fall for the participants were questioned.Results: Lower extremity function was found deteriorated (p = 0.02) and falling frequency was higher (p = 0.00) in IFA than in controls. Fatigue onset time was not different between groups, although lower extremity function was strongly correlated with fatigue onset (rho = -0.537, p < 0.001). IFA children fall four times more during running (60%), three times more during fast walking (21.42%) than their healthy peers (14.28%, 7.14% respectively). Significance: IFA leads functional problems, especially in the form of high falling frequencies. According to the LEFF score, the most difficult functional parameters for these children were walking long distances, becoming tired, walking more than a mile, and standing on one spot. Also, shorter fatigue onset time may worsen the lower-extremity function secondarily. Because of the higher frequency of falling and functional problems, children with IFA may be more defenseless to injuries, especially in high-motor-skill activities such as running and soccer.
Keywords: Femoral Anteversion; Function; Fatigue; Fall; Femoral Anteversiyon; Fonksiyon; Yorgunluk; Sonbahar